Pengaruh Pengangguran, Kemiskinan, Indeks Pembangunan Manusia, dan Populasi Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Tengah - Dhinnessa Prabowo; Masruri Muchtar; Pardomuan Robinson Sihombing (Future Science, 2023)
The success or downturn of a country's economy can also be measured by its economic growth rate. This study aims to analyze the influence of unemployment rate, poverty, human development index, and population on economic growth, especially in 14 districts/cities of Central province. Kalimantan for the period 2017-2019. The technique used is a regression analysis of panel data with the best model being the fixed effects model (FEM). The test results show that all variables simultaneously affect economic growth. Partially, unemployment and HDI have negative and insignificant effects on economic growth. Second, poverty has a negative and significant impact while the population has a positive and significant impact on economic growth. Based on the findings of this study, it is recommended from the findings of this study that policies are needed to reduce poverty while increasing population so that economic growth can continue to increase.